Regenerative braking of dc motor with renewable sources using bi-directional converter - V.C Shanmugapriyaa , S.P.Raghavel, S. Rebekah Eunice Ruby N.Hariharan , N.Kalaiarasi (International Journal of Scientific Research and Management (IJSRM), 2014)
Our main objective is to design a system using various forms of energy like solar energy, wind energy, fuel cell, etc., A new technique called multiport is introduced to select a reliable source and direct the other sources for charging the battery. A bi-directional converter is used to boost the input voltage to the required voltage. Varying input voltage switches the bi-directional dc-dc convertor to boost or buck mode. In addition, a regenerative breaking system is used which uses the motor back emf developed during braking is used to recharge the battery. This leads to the efficient usage of the available fuel